Identification of Clonal Neoantigens Derived From Driver Mutations in an EGFR-Mutated Lung Cancer Patient Benefitting From Anti-PD-1 - Wu, Di; Liu, Yangyang; Li, Xiaoting; Liu, Yiying; Yang, Qifan; Liu, Yuting; Wu, Jingjing; Tian, Chen; Zeng, Yulan; Zhao, Zhikun; Xiao, Yajie; Gu, Feifei; et al. (Frontiers in Immunology, 2020)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have been recommended as the first-line therapy for non-small cell lung cancer (NSCLC) patients harboring EGFR mutations. However, acquired resistance to EGFR-TKIs is inevitable. Although immune checkpoint blockades (ICBs) targeting the programmed cell death 1 (PD-1)/PD-ligand (L)1 axis have achieved clinical success for many cancer types, the clinical efficacy of anti-PD-1/PD-L1 blockades in EGFR mutated NSCLC patients has been demonstrated to be lower than those without EGFR mutations. Here, we reported an advanced NSCLC patient with EGFR driver mutations benefitting from anti-PD-1 blockade therapy after acquiring resistance to EGFR-TKI. We characterized the mutational landscape of the patient with next-generation sequencing (NGS), and successfully identified specific T cell responses to clonal neoantigens encoded by EGFR exon 19 deletion, TP53 A116T and DENND6B R398Q mutations. Our findings support the potential application of immune checkpoint blockades in NSCLC patients with acquired resistance to EGFR-TKIs in the context of specific clonal neoantigens with high immunogenicity. Personalized immunomodulatory therapy targeting these neoantigens should be explored for better clinical outcomes in EGFR mutated NSCLC patients.